TOXICITY OF BINARY COMBINATION OF SARACA ASOCA AND THUJA ORIENTALIS WITH SYNERGIST PIPERONYL BUTOXIDE AND MGK-264 AGAINST THE FRESHWATER SNAIL LYMNAEA ACUMINATA - SINGH, ARUNDHATI; KUMAR, PRADEEP; D. K. SINGH; V. K. SINGH (The Bioscan, 2010)
The molluscicidal activity of leaf/ bark of Saraca asoca, leaf/fruit of Thuja orientalis and their active components/ column purified fraction with synergist Piperonyl butoxide (PB) and MGK-264 (ENT 8184) were studied in binary combination (1:5) against Lymnaea acuminata. Combination of S. asoca leaf/ column extract of S. asoca leaf or bark with PB or MGK-264 is more toxic than their single treatment. Highest degree of synergism i.e.323 times was observed in the combination of S. asoca leaf with PB or MGK-264 at 96h exposure period. Combination of T. orientalis leaf/ thujone or fruit powder/ column extract of T. orientalis fruit with PB or MGK-264 indicate that it enhance the toxicity up to 189.02 times. Toxicity of binary combination was increased hundreds folds than their individual components indicating synergistic action